Alta proporción y factores asociados a depresión en estudiantes de medicina de una universidad, Honduras - Ana Ligia Chinchilla Mejía; Greybi Jackson; Marisol Maradiaga; Jorge Pineda; Norman Gustavo Morales; Jury Rosibeth Sánchez Reyes; Sayda Lizeth Pejuán Uclés; Mercedes Emelinda López Turcios; Claudia Huete; María Concepción Aguilar; Isnaya Suyapa Nuila Zapata; José Donaldo Sagastume Muñoz; et al. (Revista Médica Hondureña)
Introduction: Depression is a common mental disorder and a leading cause of disability worldwide. Objective: To determine the prevalence of depression and related factors in me-dical students. Methods: quantitative, cross-sectional descriptive study with association analysis, in students from second to seventh year of medicine, Faculty of Medical Sciences, National Autono-mous University of Honduras. The universe was 3928 students. The sampling was non-probabilistic by convenience; 282 students answered the evaluation instruments. The Beck Depression scale measured and classified the degree of depression. Results: The proportion of depression was 74% (CI 95%, 69-79). Among the participants, 31% (87) students have suicidal ideation and 6% (17) have attempted suicide. Factors that increased the risk of de-pression: being single 96.1% (OR = 4.0, CI 95%, 1.5-10.7); being economically dependent 82% (OR = 2.1, CI 95%, 1.1-3.8); female sex 68% (OR = 3.2, CI 95%, 1.8-5.6); having a family history of depression 52% (OR = 2. 0, CI 95%, 1.2-3.6); having suffered from violence 45% (OR = 3.1, CI 95%, 1.6-5.8); being affected by vio-lence 32% (OR = 4.4, CI 95%, 1.9-10.2); having been diagnosed with depression 21% (OR = 9.2, CI 95%, 2.2-39.0). Discussion: The results of this study show a high proportion of depression in this population, in comparison with similar studies that report 9.3-55.9%. This should be an alarm to expand research and generate strategies to prevent depression.